Correction of measured charged-particle spectra for energy losses in the target – A comparison of three methods - Söderberg, J.; Dangtip, S.; Alm Carlsson, G.; Olsson, N. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2002)
The experimental facility, MEDLEY, at the The Svedberg Laboratory in Uppsala, has been constructed to measure neutron-induced charged-particle production cross-sections for (n, xp), (n, xd), (n, xt), (n, x 3He) and (n, xα) reactions at neutron energies up to 100 MeV. Corrections for the energy loss of the charged particles in the target are needed in these measurements, as well as for loss of particles. Different approaches have been used in the literature to solve this problem. In this work, a stripping method is developed, which is compared with other methods developed by Rezentes et al. and Slypen et al. The results obtained using the three codes are similar and they could all be used for correction of experimental charged-particle spectra. Statistical fluctuations in the measured spectra cause problems independent of the applied technique, but the way to handle it differs in the three codes.